Yes, please! No, thank you business etiquette social skills and protocol - Badejo, Atinuke (Leicestershire Matador, 2012)
Everyone needs some form of finishing touch in their lives. Like a Grand Marnier Souffle still rising in the oven, most people are not there yet. Those who speak well may not necessarily be good with social graces. Some people have difficulties in figuring out the nuances of formal dinners or what to wear to such occasions. If you have therefore ever wondered about the difference between a 'Black Tie' and a 'White Tie' event, or if you want to know the essentials of 'how to be a lady', 'how to be a gentleman', and 'the art of dining' you will be served a full menu in this book. For young professionals, a good degree is no longer sufficient to give the competitive edge needed in our rapidly changing, demanding and hyper-competitive business environment. Most graduates therefore require additional skills to differentiate themselves. Yes Please, No Thank you offers young people starting out in life simple but enduring ways on how to communicate with confidence and position themselves for success.
Keywords: Business etiquette